Regional Incidence of Carcinoma Stomach in Bangladesh: A Prospective Observational Study (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Carcinoma of the stomach is one of the most common cancers and the second common cause of cancer related death worldwide. Over one million cases of gastric cancer are diagnosed each year around the world. The incidence is increasing day by day in the whole world as well as in Bangladesh.Objectives: The objective of this study was to find out the incidence of stomach cancer on regional basis in Bangladesh.Methods: This was a prospective observational study conducted from January to June 2012 and data were collected from general surgery ward of seven divisional medical college hospital. Patients with clinically diagnosed and positive endoscopic finding and histopathologically proved carcinoma of stomach were included in this study. History, examination and necessary investigations findings were documented in a prescribed datasheet. The Statistical Package for Social Science (SPSS) software program for windows version 17.0 was used for data analysis.Results: A total of 218 patients were enrolled in this study. The male to female ratio was 2:1. Among the patients, fifty two (23.9%) cases were from Dhaka divisions and fifty one (23.4%) from Chittagong division. About 56 (25.7%) patients were farmer. Out of 218 patients, 135 (61.9%), 16 (7.3%), 4 (1.8%) and 10 (4.8%) had history of smoking, alcohol intake, spicy food ingestion and salted food ingestion, respectively.Conclusions: The distribution of patients suffering from gastric cancer was not uniform throughout the country. The male elderly people coming from low socioeconomic status were more vulnerable for developing carcinoma stomach.J Shaheed Suhrawardy Med Coll 2024; 16(1): 48-51